ANALISIS PENGARUH HARGA JUAL SUSU TERHADAP TINGKAT PRODUKSI DAN KEMAMPUAN PEMBIAYAAN PAKAN TERNAK PADA USAHA PETERNAKAN SAPI PERAH (Studi Kasus Peternak Sapi Perah di Lingkungan KAN Jabung) - Nugraha, Dimas Sigi; SE, Sasongko (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aimed to: determine how Cooperative Agro Commerce (KAN) Jabung improve the welfare of members, determine the influence of the selling price of milk to the level of production of farmers, and determine the influence of the selling price of milk and dairy cattle ownership to the financing ability of animal feed owned by ranchers .. method used is quantitative research after the data are estimated using the OLS method. The dependent variable in this study is the level of production and financing ability fodder. While the independent variable selling price of milk and dairy cattle ownership. Results showed a significant effect on the selling price of milk at the production level, so that when an increase in the selling price of milk, offers a response to rise. And the selling price of milk and dairy cattle ownership significantly affect the ability to finance fodder. Keywords: Dairy Cattle Breeders,Cooperative, Fresh Milk Price, IPS.